2018
DOI: 10.1080/02786826.2018.1500013
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette-generated aldehydes: The contribution of e-liquid components to their formation and the use of urinary aldehyde metabolites as biomarkers of exposure

Abstract: Electronic cigarettes (e-cigarette) have emerged as a popular electronic nicotine delivery system (ENDS) in the last decade. Despite the absence of combustion products and toxins such as carbon monoxide (CO) and tobacco-specific nitrosamines (TSNA), carbonyls including short-chain, toxic aldehydes have been detected in e-cigarette-derived aerosols up to levels found in tobacco smoke. Given the health concerns regarding exposures to toxic aldehydes, understanding both aldehyde generation in e-cigarette and e-ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 64 publications
3
61
0
1
Order By: Relevance
“…We found no evidence of significant differences in exposure to the other VOCs, including acrolein, across device types. This observation regarding acrolein was surprising because vaping machine studies have reported substantial acrolein generation from e-cigarettes, particularly at higher power settings (38)(39)(40). However, it is possible that background exposure to acrolein, primarily from food sources through thermal breakdown of animal and vegetable fats, carbohydrates, and amino acids, or even endogenous production of acrolein (41), could overwhelm the contribution of e-cigarettes to acrolein exposure.…”
Section: Discussionmentioning
confidence: 99%
“…We found no evidence of significant differences in exposure to the other VOCs, including acrolein, across device types. This observation regarding acrolein was surprising because vaping machine studies have reported substantial acrolein generation from e-cigarettes, particularly at higher power settings (38)(39)(40). However, it is possible that background exposure to acrolein, primarily from food sources through thermal breakdown of animal and vegetable fats, carbohydrates, and amino acids, or even endogenous production of acrolein (41), could overwhelm the contribution of e-cigarettes to acrolein exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that e-cigarette devices could generate carbonyl compounds, thus increasing pulmonary oxidative stress and inflammation (Cirillo et al 2019 ; Ong et al 2012 ). Carbonyl levels are device specific, depending on the puffing regimen or device setup (Margham et al 2016 ; Thomson and Lewis 2015 ) the applied voltage and temperature of the heater coil (El-Hellani et al 2018 ; Gillman et al 2016 ; Kosmider et al 2014 ; Sleiman et al 2016 ), and the chemical composition of the liquids in the e-cigarette devices (Conklin et al 2018 ). In CS, carbonyls are generated during pyrolysis, combustion and distillation of the tobacco smoke product, which reaches temperatures up to 900℃ (Baker et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…As acetate is the primary urinary metabolite of AA, it was measured by GC-MS in electron ionization (EI) mode as described previously (Kage et al, 2004; Lamarre et al, 2014) with modifications (Conklin et al, 2018). Briefly, urine (50 μL) was mixed with sodium phosphate (20 μL 0.5M, pH 8.0) containing an internal standard ( 13 C 1 D 3 -acetate, 2.3 mM).…”
Section: Methodsmentioning
confidence: 99%